Improving the Quality of Health Services Through Optimizing Standard Operating Procedures (SOP) at AR-ROYYAN Hospital, Ogan Ilir Regency - Ardha, Dea Justicia; Pettanase, Ismail; Rani, Febrina Hertika; Syamsul, Syamsul; Hans, Stanislaus Wisnu Putra (Unram Journal of Community Service, 2025)
There is a lack of adequate understanding regarding health service quality through the optimization of Standard Operating Procedures (SOP) at AR-ROYYAN Hospital, Ogan Ilir Regency. This service activity aims to enhance the hospital's understanding of improving health service quality by optimizing SOPs. A visual presentation using slides and supporting materials was employed to clarify the SOPs at AR-ROYYAN Hospital. This was followed by a Q&A session to facilitate direct interaction between speakers and participants, allowing for further clarification. Engaging small discussion groups stimulated the exchange of opinions and fostered a shared understanding. Additionally, brochures and pamphlets were distributed to help participants comprehend and disseminate the information within the community. This holistic approach is expected to yield a positive and sustainable impact. The Q&A session and discussions revealed that while AR-ROYYAN Hospital has established good SOPs, these procedures have not been specifically classified for each department